Has Anything Changed in the Frequency of Emergency Department Visits and the Profile of the Adolescent Seeking Emergency Mental Care during the COVID-19 Pandemic? - Valentina Ferro; Roberto Averna; Manuel Murciano; Umberto Raucci; Sebastian Cristaldi; Anna Maria Caterina Musolino; Maria Pontillo; Nicoletta Della Vecchia; Milena Labonia; Mara Pisani; Maria Laura Pucciarini; Raffaella Nacca; et al. (MDPI AG, 2023)
We described changes caused by the COVID-19 pandemic in the frequency of Emergency Department (ED) visits for mental health disorders (MHDs) in adolescents on a wider temporal range-that is, not just "the waves" of the pandemic-and characterized the profile of the adolescent seeking emergency psychiatric care. We conducted a retrospective longitudinal study by analyzing ED visits for MHDs from 10 March 2019 to 10 March 2021. A total of 1407 ED visits for MHDs were registered: 702 in the pre-COVID-19 and 707 in the COVID-19 period. The cumulative incidence of ED visits for MHDs was 1.22% in the pre-COVID-19 period and 1.77% in the COVID-19 period, with a statistically significant difference (p < 0.001). The principal characteristics of the adolescent with MHDs during the pandemic period: the odds of comorbidities decreased by 26% (p = 0.02), and the odds of transfer from other hospitals decreased by 71% (p < 0.001), while the odds of the ED presentation as first psychiatric episode were twice greater (p < 0.001). The risk of hospitalization increased by 54% (p = 0.001). Regarding psychopathology, the likelihood of attempted suicide increased by 74% during the pandemic (p = 0.02). The rate of mood and eating disorders grew significantly during the COVID-19 pandemic period (p = 0.005 and p = 0.031, respectively). Monitoring ED visits for MHDs and understanding changes in the profile of adolescents presenting to ED helps to reinforce the role of ED in identifying special clinical needs for these vulnerable patients in case of a future public health crisis.